EKSISTENSI KEADILAN DALAM KONSTITUSI - kartika, adhitya widya (Veritas et Justitia, 2018)
Any forest ecosystem, as part of the natural environment is home to diverse animal and plant life. But existence of forest, especially rain forest, are threatened by the need to meet human insatiable demands. The constitution, on the other hand, demands the preservation of forest environment (inclusive protecting the human rights to a clean and healthy environment), the management of which is entrusted to central as well as regional-local government. Using the concept of justice as a key point, the conflict between the need to preserve and exploitation of forest resources to meet human needs shall be discussed here. This paper, using a library research and juridical dogmatic approach, attempts to trace how environmental justice is perceived in the context of the above conflicting demands.